African buffalo and colonial cattle: Is Systems Change the best future for farming and nature in Africa? - (:unkn) unknown (My University, 2023)
Much of the narrative for land clearing of wildlife is historic and frequently blames buffalo for livestock diseases, a dogma perpetrated throughout colonial history and inherited by emerging African states after decolonization. A review of this dogma indicates that the many significant problems for wildlife and cattle are related to introduced exotic livestock breeds that brought their diseases into Africa and the production and trade models that came with them. Reproducing European economic agricultural systems in Africa has failed in most African countries so far, challenging us to reconsider current agricultural economic development models in the context of human-induced global ecological changes, human relations to nature and our planetary limits. The next generation of African farmers, wildlife managers and policymakers have the opportunity to frame new coexistence and productive models between wildlife, including African buffalo, and livestock-based agriculture in the ecosystems in which they have coevolved.
Keywords: African Research